The effectiveness of decision making in the development of enterprise personnel - Karbetova, Z.; Karbetova, Sh.; Otyzbayeva, K.; Syzdykova, K. (BUKETOV BUSINESS REVIEW, 2019)
Today, the urgency of developing ways to increase the efficiency of making and implementing decisions in the development of enterprise personnel include the quality and level of enterprise management in modern conditions and they can be measured by the ability of employees to make decisions in a timely manner and organize their implementation within the required time frame. The management process in the enterprise is a process of continuous adoption and implementation of management decisions. The purpose of the analyzed enterprise LLP «Trans Serves Group» is to meet the needs of the population for quality products, works and services for greening the territory of the city of Almaty, building residential houses and maximizing profit volumes of the enterprise and implementing a growth strategy for production and marketing activities. We have conducted a study on theoretical aspects of development and decision making in the field of developing the potential of employees of LLP «ATS Trans Group». All methods of development and decision making in the assessment of enterprise personnel have been investigated; the effectiveness of development and decisionmaking in the field of personnel management were analyzed, the ways of improving their efficiency are identified, recommendations for improving the efficiency of personnel decisions were developed, sociological studies of the effectiveness of decisions on the development of personnel in the enterprise were conducted and an economic assessment of measures to improve the efficiency of personnel decisions in the company LLP «ATS Trans Group» was given.